Analisis Biaya Sistem Tebang-Angkut pada Pemanenan Tebu Bakar di PT. Gula Putih Mataram, Lampung Utara - Agus Haryanto; Sugeng Triyono; Eka Oktaviani (Jurnal Keteknikan Pertanian, 2001)
The objective of this research was to calculate the cost of harvesting and transportation methods for sugar cane. The research was conducted at the PT. Gula Putih Mataram by observe the total cost of four methods of harvesting and transportation of sugar cane in the last harvesting season. These types were Bundle Cane (BC), Loose Cane with truck (LC-Truck), Loose Cane with Ford tractor (LC-Ford), and Loose Cane with John Deere tractor (LC-JD). The results showed that the total cost of harvesting and transportation per ton of sugar cane was Rp. 19,040.00 for the first method, Rp. 12,078.32 for the second one, and Rp. 27,631.12 for the third one and Rp. 36,500.86 for the last one. These results indicate that the Loose Cane with truck is the cheapest method for harvesting and transportation in PT. Gula Putih Mataram.